2015
DOI: 10.1038/srep18356
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of US-CT image fusion to identify the sources of abnormal vascularization in posterior sacroiliac joints of ankylosing spondylitis patients

Abstract: Ultrasound (US) can be used to evaluate the inflammatory activity of the sacroiliac joints (SIJs) in ankylosing spondylitis (AS) patients, but to precisely locate the abnormal vascularization observed on color Doppler US (CDUS) was difficult. To address this issue, we performed US and computed tomography (CT) fusion imaging of SIJs with 84 inpatients and 30 controls, and then assessed the sources of abnormal vascularization in the posterior SIJs of AS patients based on the fused images. Several possible factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A few previous publications have suggested a possible role of Doppler US in determining active sacroiliitis in adults [8][9][10][11][12][13][14][15][16][17][18][19], demonstrating a high specificity of this examination, in comparison with MRI as gold standard, and proposing it as a screening method for patients with inflammatory back pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few previous publications have suggested a possible role of Doppler US in determining active sacroiliitis in adults [8][9][10][11][12][13][14][15][16][17][18][19], demonstrating a high specificity of this examination, in comparison with MRI as gold standard, and proposing it as a screening method for patients with inflammatory back pain.…”
Section: Discussionmentioning
confidence: 99%
“…The US examination of SIJs was performed as described in previous papers [8][9][10][11][12][13][14][15][16][17] (Figure 1A). The probe was positioned in transverse scan over the median line of the sacrum, at the spinous apophysis of first sacral vertebra.…”
Section: Procedures and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found CDUS to have an 82% sensitivity and 92% specificity for identifying abnormal flow in patients with AS [ 31 ]. US and CT can also be utilized together to improve the overall image and get a better look at where abnormal vasculature occurs in the SIJ [ 32 ]. CT provides the added benefit of providing a higher-resolution image than the US and can provide specific anatomical information on irregular blood flow in patients with AS [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…This technology allows improved navigation with hand-swept imaging and has demonstrated use in a range of specialties including liver, 4,5 prostate, 6,7 and breast 8 procedures. There has also been recent interest with regard to musculoskeletal applications [9][10][11][12][13] with real-time fusion being used to guide sacroiliac injections in vitro and vivo 9,10 and guide biopsy of musculoskeletal tumors. 13 Despite this, a clear role for the technology remains yet to be established in musculoskeletal intervention.…”
mentioning
confidence: 99%